Electrical behavior of Bi0.95Nd0.05FeO3 thin films grown by the soft chemical method - Destro, F. B. [UNESP]; Moura, F.; Foschini, C. R. [UNESP]; Ranieri, M. G. [UNESP]; Longo, E. [UNESP]; Simoes, A. Z. [UNESP] (Elsevier B.V., 2014)
This paper focuses on the electrical properties of Bi0.95Nd0.05FeO3 thin films (BNFO05) deposited on Pt/TiO2/SiO2/Si (100) substrates by the soft chemical method. A BNFO05 single phase was simultaneously grown at a temperature of 500 degrees C for 2 h. Room temperature magnetic coercive field indicates that the film is magnetically soft. The remanent polarization (P-r) and the coercive field (E-c) measured were 51 mu C/cm(2) and 65.0 kV/cm, respectively, and were superior to the values found in the literature. XPS results show that the oxidation state of Fe is purely 3+, which is beneficial for producing a BNFO05 film with low leakage current. The polarization of the Au/BNFO05 on Pt/TiO2/SiO2/Si (100) capacitors with a thickness of 230 nm exhibited no degradation after 1 x 10(8) switching cycles at a frequency of 1 MHz. Experimental results demonstrated that the soft chemical method is a promising technique for growing films with excellent electrical properties, and can be used in various integrated device applications. (C) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Chemical synthesis; Electron diffraction; Ferroelectricity; Thin films